GUA WURU: FUNGSI DAN JENIS PEMANFAATANNYA DI KAWASAN PRASEJARAH GUNUNG SEWU BAGIAN BARAT - Alifah Alifah (Berkala Arkeologi, 2015)
Wuru cave which located in Jetis, Saptosari Gunung Kidul, is one of the horizontal caves that contain archaeological data. This cave have a relatively small room, elongated and curved, but in this cave has many ecofact, some of which indicate the presence of human treatments (burned and trimmed). In the quality of the bone ecofact most have begun to experience the process of fossilization. In addition there is also finded shells, pottery, hazelnut and coal. These findings show evidence that the Wuru cave has potential as a cave who ever used in the past. But what kind of use or functionality of this cave in the surrounding area of Gunung Sewu western part is still unknown. This paper seeks to uncover the environmental approach, the method used is the analysis of artifacts, ecofact, and ecology around the area of the cave.